A Guide to Developing Domestic Carbon Crediting Mechanisms - Partnership for Market Readiness (World Bank, Washington, DC, 2021)
This guide to developing domestic carbon crediting mechanisms is intended to assist national and subnational policymakers considering whether and how to establish a carbon crediting mechanism in their jurisdiction. The guide provides insights into the decision points for designing a crediting mechanism and how to tailor the mechanism to achieve domestic policy objectives. This guide is divided into 10 chapters representing the key elements that must be considered when setting up a domestic crediting mechanism. These chapters should be seen as the building blocks for developing a crediting mechanism, rather than linear steps in a decision-making process. Policymakers can decide on issues simultaneously or in a different order than envisioned to suit the specific circumstances of jurisdiction.